An empirical examination of factor influencing youth travellers’ intention in selecting Muslim-friendly tourism - Md Shariffudin, Fatin Nawwarah; Md Sawari, Siti Salwa (2019)
Muslim Friendly Tourism (MFT) is currently seen as a significant segment of international tourism and has been very popular in recent years. The trend is growing as more Muslims undertakes travel to international destinations, and it is not limited to visit to pilgrimage centers like Mecca and Medina only. The Muslims are encouraged to go on travel as to witness the beauty of the creation of Allah and emulate the feeling of humbleness upon His greatness. Thus, this paper aims to investigate a factor that give the most impact towards youth intention in MFT. This study is quantitative in nature. A total of 150 respondents from the Kulliyyah of Languages and Management participated in this research. The data was analyzed by using IBM Statistical Package for Social Science (SPSS) version 21 using multiple regression analysis. The outcomes of this study show the most important factor that is the most influential for the youth to select MFT is the perceived behavior control. For future studies, it is recommended to include students from other kulliyyah and later be expanded to other institution or universities with youth travellers.